Le contrat sexuel - Pateman, Carole (La Découverte, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »– Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

Lessons in Self-Defense: Gender Violence, Racial Criminalization, and Anticarceral Feminism - Thuma, Emily (Women's Studies Quarterly, 2015)
Keywords: 1900-1999; 1980-1989; afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; féminisme autochtone; féminismes noirs; histoire; injustice; intersectionnalité; militance; patriarcat; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; résistance; sciences humaines; systèmes d'oppressions; thématiques; viol; violences; violences d'état; violences sexistes et sexuelles; états-unis; études de genres

Médecine et sexualité, aperçus sur une rencontre historiographique (Recherches francophones, époques moderne et contemporaine) - Chaperon, Sylvie; Hanafi, Nahema (Clio. Femmes, Genre, Histoire, 2013)
Cet article rappelle dans quelles circonstances une histoire de la sexualité construite à partir de sources médicales a émergé en France dans les années 1970. Il insiste surtout sur les pionnier-e-s de cette histoire pour les périodes moderne et contemporaine et les sources qu’ils et elles ont utilisées. Enfin il met en avant le renouvellement récent de ce champ grâce à une histoire « par en bas ».
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; justice sociale; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

Retour sur un attentat antiféministe : École Polytechnique 6 décembre 1989 - Blais, Mélissa; Dupuis-Déri, Francis; Kurtzman, Lyne; Payette, Dominique (Les éditions du remue-ménage, 2010)
Cet ouvrage présente quelques-unes des communications prononcées en décembre 2009 à Montréal lors du colloque international La tuerie de l’École Polytechnique 20 ans plus tard: Les violences masculines contre les femmes et les féministes. Ces textes proposent des réflexions sur le sens politique de cet attentat, ses représentations dans les médias et dans la culture, ainsi que sur ses liens avec l’antiféminisme du passé et d’aujourd’hui. Un chapitre est également consacré aux pistes de réflexion élaborées par des groupes de femmes d’ici et d’ailleurs, qui aspirent à contrer l’antiféminisme et les violences faites aux femmes. Dans la foulée des événements commémoratifs organisés sous la bannière Se souvenir pour agir, cet ouvrage et le film DVD qui l’accompagne offrent des traces de cette mobilisation sans précédent. Y sont rappelés le rassemblement public du 6 décembre 2009 auquel ont pris part plus de 1 000 personnes, l’exposition des Guerrilla Girls ainsi que l’exposition thématique Parler ou se taire?, et l’événement Bleu silence qui réunissait Pol Pelletier, le duo Lambert-Chan et Sylvie Tremblay. Ce livre regroupe les textes de Mélissa Blais, Mélanie Boucher, Yanick Dulong, Micheline Dumont, Francis Dupuis-Déri, Lyne Kurtzman, Diane Lamoureux, Florence Montreynaud, Dominique Payette, Francine Pelletier, Julianne Pidduck, Richard Poulin, Judy Rebick, Sandrine Ricci et Gilbert Turp.
Keywords: 1900-1999; 1980-1989; SAC; amériques; antiféminisme; approches et analyses; canada; chantier antiféminisme RéQEF; cours; discipline; histoire et politique; militance; montréal; patriarcat; pol5185; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences; violences contre les femmes*

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

La scission politique du féminisme international sur la question du “ trafic des femmes ” vers la “ migration ” d’un certain féminisme radical ? - Toupin, Louise (Recherches féministes, 2003)
Cet article donne un aperçu de l’argumentation qui met en lumière et différencie les principales coalitions internationales féministes luttant contre ce qui est couramment appelé le « trafic des femmes ». L’argumentation mise en évidence ne touche que la définition du phénomène et le différend qui sépare les coalitions sur le sujet, ainsi que leurs stratégies respectives pour l’éradiquer. L’auteure souligne en conclusion certains tangentes du féminisme radical qui, à son avis, se voient désormais remises en cause à l’occasion du débat sur les migrations des femmes. Ce débat entraînera-t-il, à son tour, se demande-t-elle, la migration d’un certain féminisme radical ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; histoire du féminisme; histoire et politique; intersectionnalité; miitance; patriarcat; premier cycle; prostitution; périodes historiques; ressource en ligne; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; traite des femmes; travail; travail du sexe; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Pretty in punk: girls' gender resistance in a boys' subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
https://www.rutgersuniversitypress.org/pretty-in-punk/9780813526515/
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; culture populaire; entretien; ethnographie; genre; harcèlement sexuel; montréal; nouvelle-orléans; patriarcat; périodes historiques; régions géographiques; résistance; san francisco; stéréotypes de genre; systèmes d'oppressions; thématiques; violences

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
https://search.libraries.emory.edu/catalog/990005217790302486
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Microcosm - Duffy, Maureen (Virago, 1989)
À la House of Shades, Matt, un philosophe de bar, tente de donner un sens aux vies disparates qui se croisent ici : de Judy qui réserve elle-même et ses plus beaux atouts pour un amant du samedi soir, de Steve le professeur de gym qui redoute une chance. rencontre avec une élève dans cet environnement crépusculaire, et avec Matt elle-même, qui a besoin de ces échanges indirects malgré la sécurité de sa relation avec Rae et son sentiment que ce sanctuaire lesbien est aussi une prison, renforçant la culpabilité et l'éloignement des rues de la ville au-delà. Ailleurs, il y a des femmes comme Marie, prisonnière d'un mariage non désiré et incapable d'admettre sa sexualité, et Cathy, pour qui découvrir qu'elle n'est pas « la seule au monde » est une affirmation de son existence. Avec sa structure et son style innovants, reflétant parfaitement les voix et les expériences des femmes contraintes par la société à vivre en marge, The Microcosm reste aussi puissant aujourd'hui que lors de sa première publication en 1966.
Première édition: 1966
Keywords: 1900-1999; 1960-1969; approches et analyses; hétérosexisme; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; roman; sexualité; systèmes d'oppressions; thématiques; travail; violences

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)
https://www.persee.fr/doc/grif_0770-6081_1986_num_34_1_1698
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Pornography, civil rights, and speech. (the 1984 Francis Biddle Memorial Lecture, Harvard Law School, April 5, 1984) (transcript) - MacKinnon, Catharine A. (Harvard Civil Rights-Civil Liberties Law Review)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; corps; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis